The implications of ICT adoption in the Malaysian civil courts: with special reference to the legal position in England and Wales / Ani Munirah Mohamad - Mohamad, Ani Munirah (2016)
The ICT adoption in the Malaysian courts has been problematic and raises several implications, involving both legal and non-legal ones, such as technical,organisational and social. Previous research in Malaysia had not addressed the said implications. Within this context, the central arguments of this research are two-folds:firstly, the implementation of ICT in the Malaysian courts has impacted not only on the users and courts but also raises a variety of legal, technical, organisational and social implications. Secondly, the lack of legal sanctions to most of the existing ICT applications in the Malaysian courts suggests that law will eventually lag far behind technology and will remain so in the near future. Guided by this thesis, this study aims at examining the implications of ICT adoption in the Malaysian courts on the users and the courts; the implications of the ICT adoption on the laws in Malaysia as compared to that in England and Wales; the theories of unified acceptance and use of technology and risks perception in informing the research; and to propose for the strengthening and improving the delivery of the justice system in the Malaysian civil courts through ICT adoption. Adopting a qualitative research, this study engaged both the primary data obtained from five case studies and the secondary data obtained using the doctrinal approach. The evidence from the research is extensively reported in Chapter Five. The doctrinal analysis of the legal implications of the adoption of ICT in the courts in the United Kingdom as well as Malaysia is presented in Chapters Three and Four respectively. The research found that there are various implications of ICT adoption in the Malaysian courts, as well as the courts in England and Wales, involving both legal and non-legal implications. The research further found that the theories of UTAUT and risks perception have rightly mediated the understanding of the researcher of the benefits and risks involved in the adoption of ICT at the courts. And finally, the research also found that the existing laws in Malaysia involving the Rules of Court 2012 and the Criminal Procedure Code would need to be reviewed on the rules encouraging ICT, electronic legal service of court documents, electronic filing by e-mail, court recording, audio and video conference and proper handling of digital signatures. This study will not only contribute to the understanding of the relevant laws surrounding the ICT adoption in the courts but also, to assist the Malaysian judiciary and the Malaysian Bar Council in dealing with the risks entailing such ICT adoption. Future research is suggested to be carried out using a quantitative approach to quantify such implications, the implication of ICT at other public offices such as the prison, and a comparative study to be carried out with other jurisdictions such as Australia, United States and Singapore.